Freire and experiments in conscientisation in a Bangladesh village - Rafi, Mohammad (2003)
In the 1970s most NGOs in developing countries adopted Freire's model of conscientisation to help the poor take up group action against forces resisting their development. In the late 1980s, however, this approach was discarded in favour of a micro-finance based growth-oriented one. This paper discusses BRAC, an NGO that continued its work amongst the poor, adopting Freire's conscientisation models with some modifications. - Reproduced.
Keywords: Rural development - Bangladesh; Rural development